FORMATION OF HIGH MORAL QUALITIES IN THE EPIC "FORTY GIRLS" - A.T. Saparov (Scholar Express Journal, 2021)
Karakalpak folklore is rich in all aspects and is a reflection of life. Folk epics embody the knowledge, culture, history, customs, religious beliefs, worldview, education of our people in each epoch. especially our epics are of great importance in educating the younger generation. While many epics teach young people to love their land, people and country for heroism, some epics educate them to love, kindness and friendship, and morality
Keywords: Knowledge; Culture; History; Customs